Analisis Pengaruh Reward Terhadap Kinerja Karyawan dan Penentuan Bobot Skala Prioritas Reward - Faza Adhima Suratman; Risma Fitriani (Universitas Indraprasta PGRI Jakarta, 2023)
The development of globalization in this era makes the element of human resources crucial for companies. Thus, it is necessary for companies to provide motivation and enthusiasm to employees, one of which is through rewards. PT. XYZ is a company engaged in manufacturing by making vehicle paint. The problem at PT XYZ is the low employee performance due to the lack of rewards for high-performing employees. The objective of this research is to determine the effect of extrinsic and intrinsic rewards on employee performance using multiple linear regression analysis and the priority of reward criteria using the Analytical Hierarchy Process (AHP) method. The results show that intrinsic and extrinsic rewards simultaneously affect the performance of PT. XYZ employees. The extrinsic reward variable does not significantly affect the performance of PT. XYZ employees. The intrinsic reward variable significantly affects the performance at PT. XYZ employees. Next, the results of the determination of reward priority score indicate that self-development criteria is the most expected reward criteria by employees, with a priority score of 0.39 or 39%.